3D seismic traveltime tomography imaging of the shallow subsurface at the CO2SINK project site, Ketzin, Germany - Yordkayhun, S.; Tryggvason, A.; Norden, B.; Juhlin, Christopher; Bergman, B. (Society of Exploration Geophysics, 2009)
A 3D reflection seismic survey was performed in 2005 at the Ketzin carbon dioxide (CO2) pilot geological-storage site (the CO2SINK project) near Berlin, Germany, to image the geological structure of the site to depths of about 1 km. Because of the acquisition geometry, frequency limitations of the source, and artefacts of the data processing, detailed structures shallower than about 150 m were unclear. To obtain structural images of the shallow subsurface, we applied 3D traveltime tomography to data near the top of the Ketzin anticline, where faulting is present. Understanding the shallow subsurface structure is important for long-term monitoring aspects of the project after CO2 has been injected into a saline aquifer at about 650-m depth. We used a 3D traveltime tomography algorithm based on a combination ofsolving for 3D velocity structure and static corrections in the inversion process to account for artefacts in the velocity structure because of smearing effects from the unconsolidated cover. The resulting velocity model shows low velocities of 800-1200 m/s in the uppermost shallow subsurface of the study area. The velocity reaches about 1800 m/s at a depth of 60-80 m. This coincides approximately with the boundary between Quaternary units, which contain the near-surface freshwater reservoir and the Tertiary clay aquitard. Correlation of tomographic images with a similarity attribute slice at 150 ms (about 150-m depth) indicates that at least one east-west striking fault zone observed in the reflection data might extend into the Tertiary unit. The more detailed images of the shallow subsurface from this study provided valuable information on this potentially risky area. © 2009 Society of Exploration Geophysicists. All rights reserved.